Perfluorooctanoic acid (PFOA) removal from real landfill leachate wastewater and simulated soil leachate by electrochemical oxidation process - Karatas, Okan; Kobya, Mehmet; Khataee, Alireza; Yoon, Yeojoon (Elsevier, 2022)
Poly and perfluoroalkyl compounds (PFASs) are a group of chemicals that are widely used and are difficult to purify. Within this group, perfluorooctanoic acid (PFOA), known for its highly polar and strong carbon-fluorine bonds, is a frequently encountered species in surface water, drinking water, and groundwater. In this study, we investigated the efficiency of electrooxidation (EO) in PFOA removal, optimization of EO parameters, and groundwater simulation in a realistic scenario. The EO optimization experiments were performed with a boron-doped diamond (BDD) anode for different values of pH, current density, and inlet concentration, and the effects of different anode materials were investigated for comparison. Under optimum conditions, total organic carbon (TOC) removal of up to 90% was achieved. In the groundwater simulation, we applied optimized EO parameters after obtaining leachates from the soil. A TOC removal of up to 86% was obtained in the EO of simulated groundwater contaminated with PFOA. In the case of realistic leachate simulation, four different leachate treatments were applied to PFOA-contaminated soil, and high TOC removal was achieved in all matrices. Additionally, the EO with BDD was applied to landfill leachate wastewater supplemented with PFOA to monitor the effectiveness of the process. A TOC removal of 85% was achieved, and it was observed that the number of free F-ions increased. The results showed that the BDD EO has a high potential for the treatment of PFOA-contaminated groundwater.(c) 2022 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Electrochemical oxidation; Groundwater; Landfill leachate treatment; Perfluorooctanoic acid (PFOA)